2020
DOI: 10.1002/mame.201900629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Fiber Length Distribution on Porous Sponges Originating from Short Electrospun Fibers Made from Polymer Yarn

Abstract: Recently, the potential of electrospun fibers was reported for the fabrication of novel electrospun fibrous sponges by the use of short electrospun fibers. [4,6,14,16] Owing to flexible fabrication conditions and diversified electrospun fibers, the sponges displayed tunable densities, multifunctionality, and applicability for various applications, for instance, reversible manual compression, [16] hydrophilic or super hydrophobic, [17,18] electrics, [19,20] respirable open cells, [21] or scaffolds for tissue en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Such controlled segmentation is particularly interesting in the case of polymeric fibers of microscale diameters, where the segmentation can lead to the formation of mesoscale anisotropic particles and short fibers. Such elongated particles are of interest for a range of applications, including drug delivery, phagocytosis of particles by macrophages, the formation of Pickering emulsions, and the construction of polymer sponges and aerogels. , Furthermore, the mechanism and properties that affect and control such processes, which are well rooted at the molecular level, might be easier to identify and interpret due to the relatively simpler configuration of 1D systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such controlled segmentation is particularly interesting in the case of polymeric fibers of microscale diameters, where the segmentation can lead to the formation of mesoscale anisotropic particles and short fibers. Such elongated particles are of interest for a range of applications, including drug delivery, phagocytosis of particles by macrophages, the formation of Pickering emulsions, and the construction of polymer sponges and aerogels. , Furthermore, the mechanism and properties that affect and control such processes, which are well rooted at the molecular level, might be easier to identify and interpret due to the relatively simpler configuration of 1D systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such elongated particles are of interest for a range of applications, including drug delivery, 26−28 phagocytosis of particles by macrophages, 29−31 the formation of Pickering emulsions, 32 and the construction of polymer sponges and aerogels. 33,34 Furthermore, the mechanism and properties that affect and control such processes, which are well rooted at the molecular level, might be easier to identify and interpret due to the relatively simpler configuration of 1D systems.…”
Section: Introductionmentioning
confidence: 99%
“…has drawn significant attention. [1][2][3][4][5][6][7][8][9][10] The versatility of solution electrospinning lies in its ability to produce electrospun fibers with different orientation and morphology by varying process parameters (applied voltage, receiving distance, collector type, collector speed, orifice diameter tissue engineering and biomedical applications. [38][39][40][41][42][43][44][45] The morphology, thermal, microstructural, mechanical, and viscoelastic properties of different PLA/PCL blend-based EMs have been reported in our previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…has drawn significant attention. [ 1–10 ] The versatility of solution electrospinning lies in its ability to produce electrospun fibers with different orientation and morphology by varying process parameters (applied voltage, receiving distance, collector type, collector speed, orifice diameter of needle and flow rate); electrospinning solution properties (viscosity, solvent volatility, electrical conductivity, and surface tension) and ambient conditions (temperature and humidity). [ 11 ] Further, the porous, interwoven, and continuous morphology of EMs contribute to its structural analogy with the extracellular matrix of indigenous tissues and thus act as potential candidates for the fabrication of devices for various biomedical applications such as tissue engineering, drug delivery, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) fibrous sponges made from electrospun fibers with superior mechanical and other properties have attracted increasing attention because of their superior characteristics, such as an interconnected network, light weight, low density, high porosity, hierarchical pore distribution, various material sources, and the ease with which they can be modified. These properties have resulted in 3D fibrous sponges being broadly applied in, for example, solvent absorption, cell culture, oil/water separation, thermal insulation and sound insulation, and as drug carriers and catalyst supports. However, most of these 3D sponges possess relatively weak mechanical properties. Our recent report showed that the polyacrylate-based fibrous sponges exhibited a weak compressive strength <1 kPa .…”
Section: Introductionmentioning
confidence: 99%